2001
DOI: 10.1016/s0735-1097(00)01113-x
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation for prosthetic aortic valve obstruction in the era of echocardiography: trends in diagnostic testing and comparison with surgical findings

Abstract: Doppler TTE is the primary means to diagnose AVR obstruction; hemodynamic catheterization is not routinely needed. In unselected patients with mechanical AVR obstruction, TEE differentiation of pannus or thrombus from mismatch is challenging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 24 publications
0
36
0
1
Order By: Relevance
“…2-8, 10 Girard et al reported that the incidence of previous DVR was 31% in 49 patients with reoperation for mechanical AV obstruction. 3 In that series, the cause of mechanical AV obstruction was pannus in 25 (53%), mismatch in 19 (39%), and thrombus in 4 (8%) patients. The incidence of rheumatic heart disease was only 45%.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…2-8, 10 Girard et al reported that the incidence of previous DVR was 31% in 49 patients with reoperation for mechanical AV obstruction. 3 In that series, the cause of mechanical AV obstruction was pannus in 25 (53%), mismatch in 19 (39%), and thrombus in 4 (8%) patients. The incidence of rheumatic heart disease was only 45%.…”
Section: Discussionmentioning
confidence: 80%
“…In Girard's series in which the incidence of rheumatic disease was 45%, mitral valve surgery was required in 12 (24%) and tricuspid valve surgery in 9 (18%) patients. 3 Oh et al reported an incidence of concomitant tricuspid valve surgery of 67% and of mitral valve surgery of 27% in a series of 33 cases with reoperation for subaortic pannus. 7 In our study, 16 MVRs (32%: 14 repeat, 2 primary) and 36 tricuspid valve surgeries (72%: 15 TVRs, 21 tricuspid valve repairs) were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Thromboses can be treated with thrombolysis, whereas pannus formation requires surgical intervention. Although TTE and TEE are useful modalities for evaluating the severity of valve obstruction, they are less suitable for aortic valve obstruction because of acoustic shadowing, particularly if the mass is located on the anterior side of the aortic prosthetic valve [30,31].…”
Section: Thrombosis and Pannus Formationmentioning
confidence: 99%
“…Thrombus was not seen in the ventricular aspect of On-X valve. We measured the size of thrombus with direct planimetry in diastole phase on axial views using the method of multi-planner reconstruction [8]. The area of thrombus was calculated to be 0.4 cm 2 in total.…”
Section: Casementioning
confidence: 99%